Therapeutic promises of ginkgolide A: A literature-based review (2020)
Ginkgolide A is a highly active platelet activating factor antagonist cage molecule which was isolated from the leaves of the Ginkgo biloba L. It is known for its inflammatory and immunological potentials. This review aims to sketch a current scenario on its therapeutic activities on the basis of scientific reports in the databases. A total 30 articles included in this review suggests that ginkgolide A has many important biological activities, including anti-inflammatory, anticancer, anxiolytic-like, anti-atherosclerosis and anti-atherombosis, neuro- and hepatoprotective effects. There is a lack of its toxicological (e.g. toxicity, cytotoxicity, genotoxicity and mutagenitcity) profile. In conclusion, ginkgolide A may be one of the potential therapeutic lead compounds, especially for the treatment of cardiovascular, hepatological, and neurological diseases and disorders. More studies are necessary on this hopeful therapeutic agent.